How the war in Ukraine threatens Bangladesh’s food security - Mamun, Abdullah; Glauber, Joseph W.; Laborde Debucquet, David (International Food Policy Research Institute, 2023)
As the Russia-Ukraine crisis continues to disrupt the global trade of key foods such as wheat and vegetable oils, along with fertilizers, impacts are falling heavily on countries such as Bangladesh. Dependent on imports of those items to feed its large population, many of whom are poor and vulnerable to shocks, the country faces the prospect of rising food insecurity. The conflict threatens Bangladesh’s recent progress on this front. With a population of 165 million in 2021 — with 38% employed by the griculture and fisheries sector — and a growing economy, the country’s undernourished population declined from a high of 16% in 2000 to as low as 9.7% in 2019. While the COVID-19 pandemic increased food insecurity, by some measures the country proved relatively resilient: According to an IFPRI study, the proportion of rural households facing moderate or severe food insecurity rose from 15% in early 2020 to 45% in January 2021, then returned to pre-pandemic levels by the end of 2021.